Effect of consumption of chicory inulin on bowel function in healthy subjects with constipation: a randomized, double-blind, placebo-controlled trial. (2nd January 2017) - Micka, Antje; Siepelmeyer, Anne; Holz, Anja; Theis, Stephan; Schön, Christiane
Abstract: Constipation is among the most common health impairments in Western countries. This study aimed to determine the effect of the chicory-derived fermentable dietary fiber Orafti ® Inulin on stool frequency in healthy subjects with constipation. The study was conducted according to recent guidance documents for investigating bowel function and used a randomized, double-blind, placebo-controlled, cross-over design with a 2-week wash-out phase. Each study period comprised a run-in phase followed by 4 weeks daily intake of 3 × 4g inulin or maltodextrin (placebo). Forty-four healthy volunteers with constipation documented stool frequency and consistency, gastrointestinal characteristics and quality of life. Consumption of Orafti ® Inulin significantly increased stool frequency compared to placebo (median 4.0 [IQR 2.5–4.5] versus 3.0 [IQR 2.5–4.0] stools/week, p = 0.038). This was accompanied by a softening of stools and trend toward higher satisfaction versus placebo ( p = 0.059). In conclusion, Orafti ® Inulin was effective in volunteers with chronic constipation and significantly improved bowel function. Clinical trial registration: This trial was registered at clinicaltrials.gov as NCT02548247.